IMPLEMENTASI PEMBELAJARAN PAI MELALUI MISCROSOFT TEAMS PADA SISWA KELAS VII DI SMP BRAWIJAYA SMART SCHOOL - Ardiana Ardiana (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The background of this research is to describe the implementation of Microsoft Teams and what factors support and hinder the use of Microsoft Teams in MYP learning at SMP Brawijaya Smart School. Research on the use of Microsoft Teams in MYP learning at Brawijaya Smart School uses a qualitative approach, where this approach tends to lead to descriptive research methods with case study methods. The results of this research are: 1) Planning for distance learning using Microsoft Teams in SMP Brawijaya Smart School is carried out through systematic planning, both plans made by the school or the teachers in this case especially the teachers MYP, 2) Learning Implementation MYP using the Microsoft Teams app can be implemented using existing installations in Microsoft Teams from the Introduction, Core, and Closing activities. 3) Factors that support and hinder the use of Microsoft Teams in MYP learning at SMP Brawijaya Smart School, one of the supporting factors is that the teacher can use various features in Microsoft Teams and has received training at the beginning of its use. . One of the obstacles is the internet network that does not support it.